Comic story "Uncle’s Dream": Impressions of Barnaul on F.M. Dostoevsky - Елена Юрьевна Сафронова (Philology & Human, 2018)
The article deals with the facts of the creative history of the work and the artistic attributes of the story Uncle's Dream, referring to the origin of Dostoevsky's artist's intention. Having employed the archival sources and memoirs of contemporary writers A.E. Wrangel and P.P. Semenov-Tien-Shansky, the author of the article believes that the novel reflects the impressions of F.M. Dostoevsky from visiting Barnaul . This Siberian story was originally conceived in the genre of comedy and was intended for the Barnaul stage. Besides the central «stage» plot of M.A. Moskalyova there is also a by-plot of starting a charity theatre to support the wounded and a reference to a vaudeville supposedly written by Prince K. The description of Barnaul as a hectic place with gossip and home-grown Talleyrands, which Dostoevsky gave in a letter to A.E. Vrangel, gets developed in the story, and the name of Mordasov is an allusion to an incident with Dostoevsky at the dinner at the Herngrosses house. The reference to the former employment of A.I. Moskalev, which had given him wages and benefits and had instigated the rage of an inspector, is also an allusion to Barnaul as a mining town. The periphrasis «this nasty little river with an indecent name», perhaps, refers to the river Barnaulka. There are some more local artistic attributes (hornworms, murrain, masons). Elements of self-parody are quite strong in the story: there is a travesty slant in the circumstances of marriage, meeting with P.P. Semenov and the author's disesase.